HANDBALL MEANS ROLE IN THE DEVELOPMENT OF SPECIFIC RESISTANCE FOR VTH STUDENT'S GRADE - Petrariu Ileana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The purpose of this work is to determine if the Vth graders level of resistance can develop through specific handball, having as finality achieve the objectives incumbent on "Physical Education and Sports" discipline. The work that we developed, based on an organized study of Vth grade students (28 students - 14 boys and 14 girls) from Secondary School Miron Costin from Suceava, contribute with recorded data to establish ways of specific handball methods that are effective in resistance development of students in schools. The control group consisted of 26 students (13 boys and 13 girls) from Vth grade being close in terms of numbers and about equal in terms of performance with the experimental group.